A comprehensive examination of public transport user satisfaction in Indian megacities - Rupas Kumar Meesala; M V Raju (Transactions on Transport Sciences)
In recent times, traffic congestion has emerged as a persistent problem, critically affecting travel time, fuel consumption, and commuter stress, while also contributing to poor air quality and a reduced quality of life. This global problem is especially acute in Indian megacities, which have dense populations, massive vehicular fleet, and limited road space. Although public transport is considered a promising solution to traffic congestion and related emissions, the effectiveness and adoption of road public transport depend on the characteristics of the service. This study examines commuter satisfaction with public transport services in three Indian megacities (Bengaluru, Chennai, and Hyderabad), highlighting key factors influencing user perceptions. An online survey with 2,274 respondents, divided by location, gender and age group, was conducted from January to April 2023, assessing 12 service attributes. The present study shows varied perception levels of service attributes in the three selected cities. Principal component analysis (PCA) was performed to reduce the dimensionality of the large dataset and confirm the robustness of the data, with high internal consistency across demographic variables using XLSTAT. Key factors identified in the study include ease of maintenance, accessibility, and affordability, with each city having its own strengths and weaknesses. The insights and findings of the current study provide valuable guidance for targeted improvements in public transportation systems to enhance commuter satisfaction and address the widespread problem of vehicular pollution and traffic congestion in Indian megacities.